2019
DOI: 10.1016/j.asjsur.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Does fully-threaded Headless Compression Screw provide a length-stable fixation in undisplaced femoral neck fractures?

Abstract: The FTHCSs may be a substitute for PTCSs, but it cannot prevent femoral neck shortening and varus collapse after fracture fixation. Future studies should focus on how to preserve femoral neck length and hip function after femoral neck fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…This type of fracture is dominated by shear force, which causes the proximal femur to shift and collapse during varus and is prone to internal fixation failure and other complications [28]. In recent years, the use of medial femoral neck support plate combined with cannulated screw internal fixation has been proposed for the treatment of Pauwels type III femoral neck fracture [16,29,30], which can reduce the incidence of complications, such as nonunion of femoral neck fracture and femoral head necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This type of fracture is dominated by shear force, which causes the proximal femur to shift and collapse during varus and is prone to internal fixation failure and other complications [28]. In recent years, the use of medial femoral neck support plate combined with cannulated screw internal fixation has been proposed for the treatment of Pauwels type III femoral neck fracture [16,29,30], which can reduce the incidence of complications, such as nonunion of femoral neck fracture and femoral head necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al [21] recently reported that three fully threaded headless compression screws, which were normally regarded as a non-sliding length-stable construct, failed to prevent FNS and varus collapse in Garden and femoral neck fractures compared with partially threaded screws. We think that though the patient population were all non-displaced fractures, the tendency of fracture displacement (in threedimensional orientation) may not be the same due to potential heterogeneity in fracture geometry, bone quality, etc., and thus, the universally used three fully threaded screws may not be effective in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the limited sample size and unblinded design in their study could result in unknown bias. 44 . They mainly focused on the complication rates, femoral neck shortening and the change of neck shaft angle.…”
Section: Discussionmentioning
confidence: 99%